God & progress. Religion and history in British intellectual culture, 1845-1914. By Joshua Bennett. (Oxford Historical Monographs.) Pp. xii + 311. Oxford-New York: Oxford University Press, 2019. £65. 978 0 19 883772 5 - Ledger-Lomas, Michael (The journal of ecclesiastical history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002204692000158X/resource/name/firstPage-S002204692000158Xa.jpg